A reconfigurable 38/60 GHz array antenna for 5G applications - Ahmed El Ghandour; Mohamed Nabil Srifi; Younes Karfa Bekali; Mourad El Habchi (Bulletin of Electrical Engineering and Informatics, 2026)
The aim of this paper is to propose a four-element frequency-reconfigurable antenna array operating at 38 GHz and 60 GHz for 5G applications. The proposed structure integrates three radiating elements into a single patch, enabling compactness and improved performance. The antenna achieves dual-band reconfigurability with gains of 12.65 dBi and 15.54 dBi at 38 GHz and 60 GHz, respectively. Excellent impedance matching is obtained, with S11 values of -51.82 dB and -33.79 dB at the two resonant frequencies. Frequency switching is controlled through positive–intrinsic–negative (PIN) diodes embedded in the ground-plane slot. The antenna design was modeled and validated through full-wave simulations using computer simulation technology (CST) studio suite.